Maria Rodziewiczówna o swojej twórczości. Nieznana kartka pocztowa pisarki - Rusin, Joanna (Tematy i Konteksty, 2017)
In this text an unknown before postcard by M. Rodziewiczówna has been published, in which the writer briefly yet to the point spoke on the subject of the creation of female characters and love in her novels.